2021
DOI: 10.1093/aobpla/plab002
|View full text |Cite
|
Sign up to set email alerts
|

Geographic patterns of genomic diversity and structure in the C4 grass Panicum hallii across its natural distribution

Abstract: Geographic patterns of within-species genomic diversity are shaped by evolutionary processes, life history, and historical and contemporary factors. New genomic approaches can be used to infer the influence of such factors on the current distribution of infra-specific lineages. In this study, we evaluated the genomic and morphological diversity as well as the genetic structure of the C4 grass Panicum hallii across its complex natural distribution in North America. We sampled extensively across the natural rang… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
55
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 22 publications
(59 citation statements)
references
References 62 publications
4
55
0
Order By: Relevance
“…This study provided significant evidence on the important role that epigenetic diversity may have to account for adaptation, but also highlighted the complex role of epigenetic variation as a source of phenotypic diversity with evolutionary relevance ( Medrano et al 2020 ). Finally, Palacio-Mejías et al (2021) evaluated large-scale geographic patterns of within-species genomic diversity in the C 4 grass Panicum hallii (Poaceae) across its distribution in North America (Mexico and USA) also merging RAD sequencing and species distribution models. The authors identified genetic clusters that followed the main ecoregions of the species across its range, and pinpointed South Texas as a major hotspot of genetic diversity with the co-occurrence of all genetic clusters and admixture between the two Panicum varieties of study.…”
Section: Ecology and Genetics: Two Sides Of The Same Evolutionary Coinmentioning
confidence: 99%
See 4 more Smart Citations
“…This study provided significant evidence on the important role that epigenetic diversity may have to account for adaptation, but also highlighted the complex role of epigenetic variation as a source of phenotypic diversity with evolutionary relevance ( Medrano et al 2020 ). Finally, Palacio-Mejías et al (2021) evaluated large-scale geographic patterns of within-species genomic diversity in the C 4 grass Panicum hallii (Poaceae) across its distribution in North America (Mexico and USA) also merging RAD sequencing and species distribution models. The authors identified genetic clusters that followed the main ecoregions of the species across its range, and pinpointed South Texas as a major hotspot of genetic diversity with the co-occurrence of all genetic clusters and admixture between the two Panicum varieties of study.…”
Section: Ecology and Genetics: Two Sides Of The Same Evolutionary Coinmentioning
confidence: 99%
“…In their study, Solé-Medina et al (2020) quantified how important increasingly dry conditions may be to limit the regeneration capacity of the species, which has important implications for our understanding of global climate change on plants at wide geographical scales. Finally, Palacio-Mejías et al (2021) quantified phenotypic divergence between two P. hallii varieties (var. hallii and var.…”
Section: Ecology and Genetics: Two Sides Of The Same Evolutionary Coinmentioning
confidence: 99%
See 3 more Smart Citations